1991
DOI: 10.1021/bi00233a015
|View full text |Cite
|
Sign up to set email alerts
|

Calcium depletion from the photosynthetic water-oxidizing complex reveals photooxidation of a protein residue

Abstract: A new intermediate in the water-oxidizing reaction has been observed in spinach photosystem II (PSII) membranes that are depleted of Ca2+ from the site which is conformationally coupled to the manganese cluster comprising the water-oxidizing complex (WOC). It gives rise to a recently identified EPR signal (symmetric line shape with width 163 +/- 5 G, g = 2.004 +/- 0.005), which forms in samples inhibited either by depletion of Ca2+ [Boussac, A., Zimmerman, J.-L., & 28, 8984-8989; Sivaraja, M., Tso, J., & Dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…After three flashes, the K-edge energy was again up-shifted by 0.2 eV to reach around 70% of a steady-state level found after continuous illumination where the K-edge energy was higher by 0.9 eV than that after one flash. Since illumination of the Ca-depleted S-state gives rise to the formation of a g = 2 EPR signal [7,9,, we may conclude that the up-shift in Mn K-edge parallels the formation of the g = 2 EPR state. This view is furthermore supported by the fact that the flash pattern of the Kedge energy change subsequent to the first flash is quite similar to the reported flash pattern for the formation of the g = 2 EPR signal [9,14].…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…After three flashes, the K-edge energy was again up-shifted by 0.2 eV to reach around 70% of a steady-state level found after continuous illumination where the K-edge energy was higher by 0.9 eV than that after one flash. Since illumination of the Ca-depleted S-state gives rise to the formation of a g = 2 EPR signal [7,9,, we may conclude that the up-shift in Mn K-edge parallels the formation of the g = 2 EPR state. This view is furthermore supported by the fact that the flash pattern of the Kedge energy change subsequent to the first flash is quite similar to the reported flash pattern for the formation of the g = 2 EPR signal [9,14].…”
Section: Methodsmentioning
confidence: 90%
“…Illuminating the low-pH treated PSI1 membranes results in formation of a modified S-state as indicated by an altered multiline EPR signal , and an upshifted thermoluminescence band [8,11,12]. Further illumination of the abnormal S-state with a single flash or continuous illumination induces an EPR signal in the g = 2 region [7,9]. A quite similar EPR signal was also reported in the PSI1 membranes that were depleted of Ca by treatment with high concentrations of NaCl [13-161, and …”
Section: Introductionmentioning
confidence: 99%
“…The citrate-washed preparation was reported to be isolated in an S/ state, requiring the removal of a single electron to generate the modified S2 state. Addition of calcium to citrate-washed samples in the dark resulted in the reduction in size of the YD+ EPR signal (Sivaraja et al, 1989;Tso et al, 1991b), an effect not observed with pH 6.5 NaCl-washed samples (Boussac et al, 1989;Lockett et al, 1990) but also observed by Lockett et al (1990) in pH 8.3 NaCl-washed samples.…”
mentioning
confidence: 81%
“…Therefore, it was postulated that Cu 2+ can act also on PSII activity through interference with Ca 2+ ions. Calcium akppears to be indispensable for normal functioning of the photosynthetic akpparatus, especially at the lumen side of PSII ( Ghanotakis and Yocum 1990; Tso et al 1991; Burda et al 1995; Ramalho et al 1995), CF 0 CF 1 ( Chiang and Dilley 1989; Ramalho et al 1995) and the Calvin cycle ( Kreimer et al 1988). Excess Cu 2+ in in vitro conditions can substitute for Ca 2+ in the OEC ( Hoganson et al 1991; Šeršeň et al 1997) and in CF 0 CF 1 ( Uribe and Stark 1982), leading to a decrease of phosphorylation processes and PSII activity connected with increase of energy loss in the form of heat ( Krieger and Weis 1993).…”
Section: Introductionmentioning
confidence: 99%